Factors Related to Open Defecation Behavior in Rivers - Kobandaha, Mardiana; Sibua, Siska N; Patonengan, Gita Sandy (Omni Health Journal, 2025)
Background: Careless bowel movements are one of the unhealthy behaviors. Careless Defecation (BABS) behavior in rivers is still a problem faced by the world community, especially in developing countries including Indonesia. Objective: This study aims to find out the factors related to the behavior of open defecation in the river Methods: This type of research is quantitative with a cross sectional research design. Results: This study obtained p value = 0.275 on the knowledge factor. P value = 0.255 on the attitude factor. P value 0.350 on the factor of bowel  habit Conclusion: Based on the test results , it can be concluded that there is a relationship between the factors of knowledge, attitude, and habit of defecation and the behavior of open defecation in the river.